The Impact of Regional Differences on Elementary School Teachers' Attitudes Towards Their Students' Use of Code Switching in a South Texas School District - Guadalupe Nancy Nava Gómez; Hilda García (Universidad Nacional de Colombia, 2012)
This study focused on investigating whether the teachers' geographical distribution influences their attitudes towards their students' use of code switching. The study was guided by the following research question: Are there differences between teachers' opinions of the north elementary schools and teachers' opinions of the south elementary schools, which are predominantly Hispanic, towards their students' use of code switching? If so, why? A twenty-item structured survey was utilized. The population consisted of 279 elementary school teachers at seven Northern and seven Southern schools in the same South Texas region. The data were analyzed with descriptive statistics. Findings showed that Southern teachers had more prejudices towards code switching than those from the North, who were more receptive to this socio-cultural and linguistic phenomenon due to the ethnic makeup of their classrooms.